Nearest-neighbour-interaction model in the coupled-optical-phonon-mode theory of the infrared dispersion in monoclinic crystals: Application to Tutton salt single crystal - Ivanovski, V; Ivanovski, G (Elsevier BV, 2010)
The coupled-optical-phonon-mode theory of Barker and Hopfield of two mode interaction in isotropic crystals has been extended to monoclinic crystals. The analytical expressions for the calculation of the dielectric tensor elements in the ac crystal plane have been derived. It has been shown that the interaction dielectric model is a generalized expression of the dielectric tensor for monoclinic case when no interaction between modes is present. Also, the results of Barker and Hopfield are obtained from this more general theory, when an isotropic case is considered. In order to be able to investigate real crystals, meaning extending the interactions to a large number of pairs of modes, but at the same time to make the fitting procedure possible, a model dielectric function taking into account the interaction between modes with closest frequencies has been derived. The validity of the model obtained has been tested on a Tutton salt single crystal of K(2)Co(SO(4))(2).6H(2)O. The recorded spectra from the ac crystal plane were fitted in order to obtain best fit parameters. The comparison between the experimentally recorded spectra and the model reflectance function give good results and verify this model to be applicable.